On the Genesis of Neuroblastoma and Glioma. (26th March 2014) - de Weille, Jan
Abstract : As the emergence of cancer is most frequent in proliferating tissues, replication errors are considered to be at the base of this disease. This review concentrates mainly on two neural cancers, neuroblastoma and glioma, with completely different backgrounds that are well documented with respect to their ontogeny. Although clinical data on other cancers of the nervous system are available, usually little can be said about their origins. Neuroblastoma is initiated in the embryo at a moment when the nervous system (NS) is in full expansion and occasionally genomic damage can lead to neoplasia. Glioma, to the contrary, occurs in the adult brain supposed to be mostly in a postmitotic state. According to current consensus, neural stem cells located in the subventricular zone (SVZ) in the adult are thought to accumulate enough genomic mutations to diverge on a carcinogenic course leading to diverse forms of glioma. After weighing the pros and cons of this current hypothesis in this review, it will be argued that this may be improbable, yielding to the original old concept of glial origin of glioma.